Herpes Simplex Virus: The Hostile Guest That Takes Over Your Home - Banerjee, Anwesha; Kulkarni, Smita; Mukherjee, Anupam (Frontiers in Microbiology, 2020)
Alpha-(α) herpesviruses (HSV-1 and HSV-2), like other viruses, are obligate intracellular parasites. They hijack the cellular machinery to survive and replicate through evading the defensive responses by the host. The viral genome of Herpes Simplex Viruses (HSVs) contains viral genes, the products of which are destined to exploit the host apparatus for their own existence. Cellular modulations begin from the entry point itself. The two main gateways that the virus has to penetrate are the cell membrane and the nuclear membrane. Changes in the cell membrane are triggered when the glycoproteins of HSV interact with the surface receptors of the host cell and from here, the components of the cytoskeleton take over. The rearrangement in the cytoskeleton components help the virus to enter as well as transport to the nucleus and back to the cell membrane to spread out to the other cells. The entire carriage process is also mediated by the motor proteins of the kinesin and dynein superfamily and is directed by the viral tegument proteins. Also, the virus captures the cell’s most efficient cargo carrying system, the ER-Golgi vesicular transport machinery for egress to the cell membrane. For these reasons, the host cell has its own checkpoints where the normal functions are halted, once a danger is sensed. However a cell may be prepared for the adversities from an invading virus and it is simply commendable that the virus has the antidote to these cellular strategies as well. The HSV viral proteins are capable of limiting the use of the transcriptional and translational tools for the cell itself, so that its own transcription and translation pathways remain unhindered. HSV prefers to constrain any self-destruction process of the cell; be it autophagy in the lysosome or apoptosis by the mitochondria, so that it can continue to parasitize the cell for its own survival. This review gives a detailed account of the significance of compartmentalization during HSV pathogenesis. It also highlights the undiscovered areas in the HSV-cell biology research which demand attention for devising improved therapeutics against the infection.